A memória de um período e a verdade da história - Solon Eduardo Annes Viola; Thiago Vieira Pires (Ciências Sociais Unisinos)
This article discusses the national and international conjuncture that has produced the violence exercised by the State against society and that, until today, continues to promote the oblivion by refusing to reveal the past. In order to do that, this paper analyzes political forces in confrontation, the theoretical basis of the Cold War and its coercive practices. Besides that, it intends to relate the National Security Doctrine to the period of Military Dictatorship and it shows the struggling theories in the national memory reconstitution and the recomposition of the historical truth.